Analisis Penerapan Target Coting Dalam Upaya Efisiensi Biaya Produksi Dan Peningkatan Laba Usaha Pada Usaha Kecil Menengah - Larissa, Cindy; Rahayuningsih, Sri (SM Institute, 2024)
UD. Adon Jaya which is located at Jl. Bima, Ds. Kebonsari RT 05 RW 01, Kec. Candi, Sidoarjo Regency, East Java is a Small and Medium Enterprise (UKM) owned by Pak Sulaiman which operates in the food sector, namely salted eggs. Salted eggs produced by UD. Adon Jaya has an interesting innovation where the salted eggs have different flavors and processing methods, such as original, fried, grilled and oven flavoured. Daily sales can reach 400 to 500 salted eggs with an income of IDR 16,000,000 to IDR 18,000,000 per month with a profit percentage of 31%. The research objective to be achieved in accordance with the research questions explained above is to find out, analyze and answer how the application of target costing affects production cost efficiency and increasing business profits at UD. Adon Jaya. This research took informants from UD owners. Adon Jaya, namely Mr Sulaiman and production employee Mas Zaky. In its implementation in the field, this research took secondary data including company history, financial and sales report data, as well as an explanation of the salted egg production process. The type of research that will be used is qualitative methods. The analysis technique used is comparative analysis between manual calculations used by UD. Adon Jaya with calculations that apply target costing carried out by the author. These results show that implementing target costing can streamline production costs by 12%, so that the resulting profit also increases 37%. The results of the analysis findings conclude that the application of target costing at UD. Adon Jaya has a positive influence by streamlining production costs so as to increase profits.